Religious Values dnd School Governance: Implementing Akhlaqul Lil Banin for Bullying Prevention in an Islamic Junior High School - Eko Wahyu Junaidi; mawi mawi mawi; Aulia Sholichah Iman Nurchotimah; Varidho Fuad (Public Policy and Management Inquiry, 2026)
This study aims to analyze the internalization of the values contained in Akhlaqul Lil Banin Volume I as an effort to prevent bullying behavior among students at Madrasah Tsanawiyah Ushuluddin Singkawang. This research employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation involving guidance and counseling teachers, the vice principal for curriculum affairs, subject teachers, and seventh-grade students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings revealed that the internalization of Akhlaqul Lil Banin Volume I values was carried out through classroom learning, teacher role modeling, habituation of madrasa culture, and the integration of moral values into daily religious activities. The values internalized included respect for teachers, proper speech etiquette, humility (tawadhu'), discipline, empathy, responsibility, and mutual respect. The internalization process contributed to positive behavioral changes among students, as reflected in improved self-control, more constructive social interactions, and a reduced tendency toward verbal and social bullying within the madrasa environment. This study concludes that the internalization of Akhlaqul Lil Banin Volume I values serves as an effective preventive strategy in shaping students' character and fostering a safe, harmonious, and religious educational environment.